2015
DOI: 10.1016/j.pmedr.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of cell phone use among Texas drivers

Abstract: IntroductionCell phone use while driving restricts peripheral awareness and impairs reaction time. This study assessed the 3-year prevalence of cell phone use (CPU) of drivers and characteristics associated with its use in six cities across Texas, 2011–2013.MethodsCPU and driver characteristics were observed among motor vehicles (n = 1280) stopped at major intersections in medical and academic campuses. A multivariable logistic regression model described the association between driver characteristics and CPU.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Despite longstanding educational and enforcement efforts, mobile (cell) phone distracted driving has remained an ongoing concern in the transport system worldwide. Observational studies report that the prevalence of drivers using a mobile phone varies from 5% to 18.7% in high-income countries such as Australia and United States, and up to 31.2% in low-and middle-income countries such as Botswana and Mexico (Pheko, Tlhabano, Monteiro, & Balogun, 2013;Vera-López et al, 2012;Wilkinson, Brown, Moussa, & Day, 2015;Young, Rudin-Brown, & Lenné, 2010). Mobile phones are emergent technologies in constant evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Despite longstanding educational and enforcement efforts, mobile (cell) phone distracted driving has remained an ongoing concern in the transport system worldwide. Observational studies report that the prevalence of drivers using a mobile phone varies from 5% to 18.7% in high-income countries such as Australia and United States, and up to 31.2% in low-and middle-income countries such as Botswana and Mexico (Pheko, Tlhabano, Monteiro, & Balogun, 2013;Vera-López et al, 2012;Wilkinson, Brown, Moussa, & Day, 2015;Young, Rudin-Brown, & Lenné, 2010). Mobile phones are emergent technologies in constant evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Recent naturalistic driving estimates in the USA have confirmed that drivers are distracted in some way around half of the time, with mobile phone use making up about a quarter of the distracted time [ 5 ]. Observational on-road studies have found that nearly 18.7% in the USA [ 7 ] and 5% in Australia [ 8 ] use a mobile phone while driving.…”
Section: Introductionmentioning
confidence: 99%
“…[ 35 ] Millennials (18–34 years of age) are more likely to be mobile device users compared with those aged 35 years and older,[ 36 ] and research has consistently shown that younger drivers (<30 years) engage in distracting activities more often than older drivers. [ 4 5 6 8 9 ] Similarly, the findings of our review suggest that distracted driving-related trauma is most common among relatively inexperienced drivers, with the greatest proportion of road traffic injuries and deaths seen in the 20–30 years age group. Furthermore, Lam found the relative risk (RR) of injury or death in crashed drivers who were using a handheld phone (compared to crashed drivers with no distraction) was significantly higher in drivers aged 25–29 years (RR = 2.37), but not in any other age group.…”
Section: Discussionmentioning
confidence: 61%
“…The prevalence of distracted driving related to mobile devices use has been reported to range between 1.3% and 31.4%. [ 3 4 5 6 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%